Religious Moderation and Interfaith Harmony in Maqashid Sharia: An Analytical Study of Quranic Hermeneutics - Mustapa, Mustapa; Suardi, Indra; Kirin, Arwansyah bin (State of Islamic Institute Langsa, 2025)
Ideally, religious moderation and communal harmony should serve as the cornerstone for building a harmonious social life, particularly in diverse societies. However, the reality reveals that interfaith conflicts and a lack of tolerance still often occur, driven by narrow and exclusive interpretations of religion. This phenomenon hinders the creation of peace and harmony within pluralistic communities. This article is based on qualitative research. The methodology employed is a content analysis of Quranic verses through a hermeneutic approach. The findings indicate that maqasid shariah provides a strong foundation for promoting religious moderation and communal harmony. Values such as justice, welfare, and the protection of individual rights embedded within maqasid shariah can serve as guidelines for creating a tolerant and harmonious society. The Quranic hermeneutic approach also aids in understanding the messages of moderation contextually, enabling practical solutions to the challenges of diversity in modern society.